A look at the Current Situation of Iranian Molecular Diagnostic Methods and the Implementation of Required Future Policy: A Review Article. - Massoud Hajia (Reviews in Clinical Medicine, 2020)
Today, molecular diagnostic methods have an unignorably position in diagnostic laboratories. It is estimated that 60-70% of all decisions depend on molecular detection methods. However, many Iranian physicians still do not fully trust the newly developed protocols in particular. If necessary, they request some confirmatory tests available to ensure a final decision.The purpose of this short study is to investigate the causes of uncertainty in these tests and current challenges in Iranian clinical centers. Therefore, all the effective cases from receiving the samples to publishing the patient reports are looked up. Significant parameters including pre-analytical, analytical and post-analytical parameters are studied in this study. The reason for some of the current limitations is discussed based on released documents and reported periodic inspections according to published standard criteria. Based on the results, the need for fundamental revisions in some parts of the relevant bodies is clearly identified.